The Labyrinth. Discussing the Meaning of Its Arrangement and Notion - Rappaport, Alexander (project baikal, 2018)
The image of labyrinth reflects the complicated contemporary world and worldviews. The one who enters the labyrinth is different from the one who leaves it. It is already a reborn person. The labyrinth is a place for reincarnation. Architecture does not hide and does not exist beyond its essence. Being initially invisible, the labyrinth becomes itself in pursuit of the secret. Contemporary architecture with its artificial or natural passion for transparency, good orientation and ling-sightedness deprives the city of iconic labyrinths and wonders.